PENGARUH FAKTOR FUNDAMENTAL TERHADAP STRUKTUR MODAL (STUDI PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2011-2015) - Diana Sari, Mila; Yudiastuti, Anni (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Katolik Widya Karya Malang, 2018)
This study aimed to determine the effect of the fundamental variables of the company's capital structure included in the group of Indonesian food and beverage from 2011 to 2015 period. This study used a population selected using selection criteria and the population acquired 12 companies that deserve to be the population. The research sample used all companies included in the study population or sample selection techniques using saturated sample. This type of research is quantitative positivist approach because the emphasis on testing theories through measurements of the study variables with numbers and perform data analysis with statistical procedures. The variables used in this study were Profitability, Company?s Size, Sales Growth, and Structure Assets. The data calculation for fundamental variables was done by selecting the components of the financial statements included in the calculation formula. Testing continued with descriptive and hypothesis testing using multiple linear regression analysis in SPSS. The results of this study indicated that the variable profitability negatively affect the capital structure of food and beverage companies in Indonesia, while the size of the company has a positive effect on the capital structure of the food and beverage company in Indonesia. Variable structure asset and sales growth do not affect the capital structure of food and beverage companies in Indonesia